An applied requirement simulation model to forecast the needs of nursing services in the Malaysian health sector - Ramli, Mohamad Raziff; Abal Abas, Zuraida; Desa, Mohammad Ishak; Saleh, Nordin; Aziz, Nuraini; Shibghatullah, Abdul Samad; Abdul Rahman, Ahmad Fadzli Nizam; Zainal Abidin, Zaheera (Inderscience Publishers, 2022)
This paper aims to forecast the requirement of the nursing workforce for the next 15 years in Malaysia. Healthcare services act as a benchmark to estimate the requirement of the nursing workforce. The services were estimated based on the 11 types of preventive care and 91 diseases, which were modelled to calculate the total services required. System dynamics is used as a computer-aided approach to simulate the insight of all the models. This model results in the total number of nursing service time required to meet the requirement of healthcare services in a population. The results would be discussed with the supply model for gap analysis. The implication of the results discussed in this paper would help the planning division in the Ministry of Health Malaysia in determining the right number of nurses that are required to meet the needs and improve the health outcomes.